The Role of Sales Interns in Business Expansion - Gupta, Prasanna (ATLAS SkillTech University, 2025)
The global automotive industry is a massive and highly competitive market, valued at around $3.5 trillion in 2023 and projected to grow at a CAGR of 5-7% over the next 5 years. The industry is dominated by several multinational automakers, including Toyota, Volkswagen, Daimler (Mercedes- Benz), General Motors, Ford, Honda, Nissan, Hyundai-Kia, Fiat Chrysler, and BMW, which have a strong presence across multiple regions and product segments. Key industry trends include the increasing adoption of electric vehicles and hybrids, advancements in autonomous driving technology and connectivity features, the shift towards shared mobility solutions, and a growing emphasis on fuel efficiency, lightweight materials, and sustainable manufacturing practices. However, the industry also faces challenges such as intense competition and price pressures, compliance with stringent emission regulations, adapting to rapidly changing consumer preferences and technological advancements, supply chain disruptions, and the significant investments required for research and development. Nonetheless, the industry presents opportunities in expanding middle-class populations and rising disposable incomes in emerging markets, growing demand for affordable and technologically advanced vehicles, potential growth in the aftermarket and replacement parts segments, and increasing demand for commercial vehicles, especially in developing economies, as well as the autonomous and shared mobility sectors.
Project Report on The Role of Sales Interns in Business Expansion (2023-2025) Under the Guidance of Prof. Jaimine Vaishnav
Keywords: hybrids; electric vehicles; consumer preferences; technological advancements